Weighty metal, microbial profile and proximate of some preferred commercial marine fish collected from two markets in south western Nigeria - Chinedu, Ameachi; chika I. K; Oboroh, Nathaniel (Advances in Aquaculture and Fisheries Management, 2014)
The study on the elemental, proximate and microbial composition of fresh samples of Scomber scombrus, Gadus macrocephalus, Saclina pilchradus and Jack mackerel was determined to gain the knowledge of the risk and benefits associated with indiscriminate consumption of marine fishes. Wet digestion was done for the samples and was analyzed for minerals, heavy metals and microorganisms. The species examined contained appreciable concentrations of moisture, protein, lipids and ash content suggesting that the fish species could be used as a good source of minerals. Heavy metals analyzed were above tolerable limits; therefore, it can be suggested that taste, size, freshness and other related external appearances should not be the only factor to be considered in making choice for marketing and consumption of marine and freshwater fishes in Nigeria.